Phosphorus availability drives mycorrhiza induced resistance in tomato - Dejana, Laura; Ramírez-Serrano, Beatriz; Rivero, Javier; Gamir, Jordi; López-Ráez, Juan A.; Pozo, María J. (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal (AM) symbiosis can provide multiple benefits to the host plant, including improved nutrition and protection against biotic stress. Mycorrhiza induced resistance (MIR) against pathogens and insect herbivores has been reported in different plant systems, but nutrient availability may influence the outcome of the interaction. Phosphorus (P) is a key nutrient for plants and insects, but also a regulatory factor for AM establishment and functioning. However, little is known about how AM symbiosis and P interact to regulate plant resistance to pests. Here, using the tomato-Funneliformis mosseae mycorrhizal system, we analyzed the effect of moderate differences in P fertilization on plant and pest performance, and on MIR against biotic stressors including the fungal pathogen Botrytis cinerea and the insect herbivore Spodoperta exigua. P fertilization impacted plant nutritional value, plant defenses, disease development and caterpillar survival, but these effects were modulated by the mycorrhizal status of the plant. Enhanced resistance of F. mosseae-inoculated plants against B. cinerea and S. exigua depended on P availability, as no protection was observed under the most P-limiting conditions. MIR was not directly explained by changes in the plant nutritional status nor to basal differences in defense-related phytohormones. Analysis of early plant defense responses to the damage associated molecules oligogalacturonides showed primed transcriptional activation of plant defenses occurring at intermediate P levels, but not under severe P limitation. The results show that P influences mycorrhizal priming of plant defenses and the resulting induced-resistance is dependent on P availability, and suggest that mycorrhiza fine-tunes the plant growth vs defense prioritization depending on P availability.